Nexus of Trade, FDI, Green Energy, Green Tax and Environmental Quality in Vietnam: A Time Varying Granger Causality - Xuan, Dao Mai; Lan, Nhung Tran Thi; Thuy, Trinh Ho (International Journal of Energy Economics and Policy, 2025)
This paper explores the time-varying causal relationship between environmental quality and key economic indicators, including trade, foreign direct investment (FDI), green energy, and green tax in Vietnam over the period 2005-2020. Utilizing forward recursive, rolling window, and recursive evolving Granger causality techniques, the study reveals that the causal nexus between environmental and economic variables is dynamic and context dependent. The findings show that environmental quality does not Granger-cause trade, while it exerts short-term effects on FDI and green energy, particularly during periods of heightened environmental policy attention. In contrast, trade and green tax significantly influence environmental quality, especially in the aftermath of major policy shifts, such as the implementation of Vietnam’s environmental tax law and its commitments under the Paris Agreement. Based on the result, some policy implications are suggested to effectively navigate the evolving relationship between environmental sustainability and economic development in Vietnam.